On-bottom stability of subsea lightweight pipeline (LWP) on sand soil surface. (3rd October 2017) - Bai, Yong; Xu, Weiping; Ruan, Weidong; Tang, Jiwei
Abstract : This paper discusses the on-bottom stability of subsea lightweight pipeline (LWP) on sand soil seabed subjected to a combined load of wave and current. Hydrodynamic loads were applied on an LWP to test the on-bottom stability of the pipe. The tests of LWP were carried out with different pipe outer diameter (OD) and different pipe submerged weight. The lateral movement of pipe experiences three characteristic periods based on the lateral displacement of pipe: (1) slightly shaking with sand scour; (2) crossover sand breakouts; (3) laterally moving within a displacement of 2.0 × OD or the pipe will continue to lateral movement after the lateral displacement of 2.0 × OD. A lateral displacement of 2.0 × OD is selected as the displacement criteria for the on-bottom stability of LWP because the pipe will be continuously laterally moving in case the lateral displacement of pipe is larger than 2.0 × OD for LWP, which is different from the on-bottom stability of a rigid steel pipe. Based on the test results, an empirical correlation was established to describe pipeline's lateral on-bottom stability. Three-dimensional ABAQUS dynamic finite element simulations of an LWP on flat seabed are carried out. In accordance with the experimental observations, a modified correlation suggested in DNV-RP-F109 code is used for simulating the lateral resistance of LWP on sand soil surface. The effects of lift force on the pipe when the pipe contacts the seabed were considered. A MathCAD worksheet based on the generalised lateral stability method in DNV-RP-F109 was used to assess the pipeline on-bottom stability. The comparison results of MathCAD and finite element analysis (FEA) showed that the FEA simulation gives a good agreement with test results when the lateral pipe displacement is less than 2.0 × OD. The modified FEA model can be used for the on-bottom stability analysis of LWP to reduce conservatism.